Barriers to advancing the sexual and reproductive health agenda in Latin America: a qualitative study of key informants’ perspectives - Alonso, Juan Pedro (2024)
BackgroundThe effective attainment of sexual, reproductive, and maternal health and rights (SRMHR) requires a holistic life-course approach. This approach should address disparities in healthcare access and rights, guarantee the delivery of high-quality care devoid of discrimination, and underscore rigorous accountability mechanisms throughout the implementation process. Latin American and Caribbean (LAC) countries face significant disparities in SRMHR within and between nations. Vulnerable populations, such as indigenous communities, Afro-descendants, LGBTQI + population, persons with disabilities, older adults, and migrants, often endure discrimination and stigmatization, severely impacting their access to healthcare and health rights. This paper presents the findings from the qualitative component of a broader mixed-methods scoping study aimed at establishing a priority research agenda to address healthcare gaps affecting the SRMHR of vulnerable populations. The qualitative component focused on identifying key challenges hindering progress in SRMHR and access to health services for these populations in the LAC region, drawing on the perspectives of key informants at both regional and national levels.MethodsQualitative research approach employing semi-structured interviews with key informants. A purposive sample comprised of stakeholders from relevant regional organizations and local stakeholders in selected countries (Argentina, Colombia, Peru, Mexico, Guatemala, Jamaica, and Guyana), encompassing government representatives, civil organizations, and academia. A rapid content thematic analysis was conducted to analyze the data obtained from the interviews.ResultsWe interviewed 27 key informants in SRMHR, six at a regional level and 21 at a country level. The region faces barriers around establishing and sustaining agency agendas, such as a lack of political will, political instability, and opposition from civil society groups regarding SRMHR agendas. Policy implementation presents difficulties due to insufficient and unstable funding, weaknesses in sexual and reproductive health programs, unequal policy implementation in federal countries, and the absence of evidence-based policies. The lack of high-quality data and quality indicators poses obstacles, leading to limitations in evidence generation. Access to SRMHR services faces barriers such as the low-quality provision of services, discrepancies between legislation and effective access, insufficient healthcare resources, and resistance from certain healthcare providers.ConclusionAddressing these multifaceted challenges will be crucial in advancing the agenda of sexual, reproductive, and maternal health rights and ensuring effective access to health services for the most vulnerable populations in the LAC region.